Adsorption Study of Carbon Chitosan Composite Beads from Ketapang Fruit Shell (Terminalia catappa L) on Methylene Blue Dyes: Kajian Adsorpsi Beads Komposit Kitosan Karbon Cangkang Buah Ketapang (Terminalia catappa L) Terhadap Zat Warna Metilen Biru - Nurwidiyani, Ria; Sigiro, Chelin Dion; Putranto, Agus Martono Hadi; Triawan, Deni Agus (Department of Chemistry - Universitas Bangka Belitung, 2024)
Carbon chitosan composite beads were synthesized using chitosan and activated carbon from Ketapang fruit shells (Terminalia catappa L) using PVA as a crosslinker. The adsorbent was synthesized with a chitosan: activated carbon ratio of 0.8 grams versus 0.2 grams. Material characterization using FTIR shows the presence of C-O, N-H, C-N, C=O, C-H, and -OH functional groups. Adsorption of carbon chitosan composite beads on methylene blue achieved maximum results at a contact time of 75 minutes using an adsorbent mass of 0.15 grams with an adsorption percentage reaching 97%. The adsorption kinetics follows a pseudo second order kinetic model with a k value of 1.3467 mg-s-.